ACCOUNTING THETIME DELAY INTHEBINARY COAGULATION MODEL - Kazenova Aykerim,; Brener Arnold,; Golubev Vladimir Grigorievich,; Tashimov Lesbekov Tashimovich,; Shapalov Shermakhan Kuttibayevich,; Kenzhalieva Gulmira,; Tortbayeva Dinara Ryskulbekkyzy, (Academic Journal of Physical and Chemical Sciences, 2019)
The paper deals with the time-delayed model for cluster aggregation processes based on the Smolukhovsky equation with the help of the heat and mass transfer kernels approach. The new non-local modification of the general kinetic equation of Smoluchowski binary aggregation equation hasbeen submitted. Forthecaseof an isotropic and homogeneous medium, the model has been reduced to the ordinary differential equation. The further possible development of the proposed model with allowance for taking into account the differences in the characteristic coagulation times during the aggregation of globules of different order has been discussed.